Dose–response relationship between physical exercise and risk of physician-diagnosed dementia in 206 073 Thai community-dwelling men and women: HCUR study - P. Boongird (2020)
© 2020 European Academy of Neurology Background and purpose: Little evidence exists to describe the incidence and risk factors for dementia in developing countries. This study aimed to examine the incidence and factors associated with the risk of developing dementia in a Thai general population. Methods: Data on 206 073 men and women aged ≥50 years participating in the Health Check Ubon Ratchathani Project in 2006 were merged with diagnostic information from the hospital’s electronic medical records in the following 6 years (2006–2012). The incidence of physician-diagnosed dementia over 6 years was examined. Factors associated with the risk of developing dementia were examined using multivariate Cox proportional hazard regression. Results: Over a total time at risk of 1 196 433 person-years, 480 individuals developed dementia; the incidence rate was 0.40 [95% confidence interval (CI) 0.37–0.44] per 1000 person-years. Dementia incidence rose exponentially with increasing age to 1.37 (95% CI 1.07–1.75) per 1000 person-years in those aged 80–84 years and dropped after the age of 85 years. Factors independently associated with the risk of developing dementia included increasing age, diabetes and lack of physical exercise. The risk of dementia rose by 7% for every 1 year of age older [adjusted hazard ratio (aHR) 1.07, 95% CI 1.06–1.08]. Diabetes increased the risk of dementia by 51% (aHR 1.51, 95% CI 1.12–2.03). Compared to no physical exercise, having 3–5 days/week and> 5 days/week of physical exercise reduced the risk of dementia by 37% and 59% (aHR 0.63, 95% CI 0.50–0.79, and 0.41, 95% CI 0.26–0.66, respectively). Conclusions: Dementia incidence in a Thai population was lower than Western populations and its independent risk factors included increasing age, diabetes and a lack of physical exercise. Adequate physical exercise may counterbalance the ageing process, the main drive of dementia.